丙氨酰-谷氨酰胺强化营养支持治疗腹型过敏性紫癜患儿的临床研究 (Zhongguo Dang Dai Er Ke Za Zhi, 2019)
OBJECTIVE: To study the clinical effect of alanyl-glutamine-enriched nutritional support in the treatment of children with abdominal Henoch-Schönlein purpura. METHODS: Children with abdominal Henoch-Schönlein purpura who needed nutritional support were enrolled and stratified according to age, sex and the severity of disease, and were randomly divided into a control group (n=118) and an enriched nutritional support group (n=107). The control group was given nutritional support without using alanyl-glutamine, while the enriched nutritional support group was given alanyl-glutamine-enriched nutritional support. Intravenous steroids were used according to the severity of disease in both groups. Other therapies were the same in the two groups. The two groups were compared in terms of the length of hospital stay, the rate and duration of use of intravenous steroids, the recurrence rate of symptoms during hospitalization, the rate of total parenteral nutrition (TPN), the rate of weight loss and the rate of fasting for more than 5 days. All patients were followed up for 3 months after discharge to monitor the recurrence of symptoms. RESULTS: There were no significant differences in the length of hospital stay, the rate of TPN and the rate of fasting for more than 5 days between the two groups (P > 0.05). Compared with the enriched nutritional support group, the control group showed significant increases in the rate and duration of use of intravenous steroids, the recurrence rate of symptoms and the rate of weight loss (P < 0.05). After the 3-month follow-up, all the children resumed normal diet, and the recurrence rate of digestive symptoms was less than 20% in each group. Abdominal pain was the most common symptom (83.33%, 30/36), followed by vomiting and abdominal distention. No digestive hemorrhage was observed. All the symptoms were relieved after symptomatic treatment. No significant difference was found between the two groups in the recurrence rate of digestive symptoms (P=0.693). CONCLUSIONS: Alanyl-glutamine-enriched nutritional support in the treatment of children with abdominal Henoch-Schönlein purpura can reduce the use of intravenous steroids and weight loss, but without impact on the length of hospital stay and post-discharge recurrence.